Trends of motorcyclist accidents in Kelantan between 1998-2003 - Nik Rosmawati N.H.; Manaf A.H.; Ahmad Zaki I; Lin Naing S. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
Motor vehicle crashes (MVCs) contribute large proportion of death and disability globally and motorcyclists are the most vulnerable group. In Malaysia, motorcycles are one of the most important forms of personal transportation. More than 50% of the registered vehicles in this country are motorcycles. Casualties among motorcyclist form a large portion of traffic injury problems in Malaysia and are ranked among the highest in comparison to other countries. The objective of the stu& was to determine the trend of motorcycle crashes in Kelantan, between 1998 and 2003. This was a retrospective record review of MVCs data in Kelantan. Data gathered were input into SPSS version 11 and Microsoft Excel and analyzed using decomposition method to explore the seasonality and simple linear regression to explore the trend. The study revealed that majority of road trafic injuries involved motorcycle users (58.5% to 63.1 %). The proportion of fatality was between 8.6% and 10.7% and majority involved 11-30 years (60.0% - 69.7%). About 90% of the fatal motorcycle injuries were male. The peak hour for fatality was between 4.00 to 8.00 afternoons. No seasonal pattern of motorcycle accidents but, there was signrficant linear increasing trend (p<0.001) with an average of 9 cases increasing every year. Based on the results above, we conclude that the trend of motorcycle accidents was increasing in year 1998 - 2003, but no seasonal pattern. Most of the fatal motorcycle crashes involved young men riders and occurred at afternoon. We recommend that public education and enforcement on accident prevention should be given a priority.